Isotyping antibodies produced from hybridoma A6G11C9 - Trung, Nguyễn Thị; Hải, Trương Nam (Vietnam Journal of Biotechnology, 2018)
Hybridoma technology was discovered in 1975 to produce the monoclonal antibodies. By this way, we can produce a desired antibody in large amounts. From a single hybrid cell line, they grow and develop to produce a monoclonal antibody with large enough quantities to use for the research, treatment and diagnosis. The level of the antibody producing is depended on the cell density and the incubation period. The growth capacity of each hybrid cell line depends on the composition of the substances in the culture medium of animal cells. Among them, fetal bovine serum is the most commonly used serum-supplement for the in vitro cell culture. This is due to it having a very low level of antibodies and containing more growth factors. In the previous studies, the hybrid cell line (designed A6G11C9) was the best one secreting the highest anti-A monoclonal antibodies, whose specificity agglutinaned human red blood cells containing A antigen. This report showed the result of the study on the coditional culture and isotyping of the immunoglobulin. The hybrid cell line A6G11C9 was cultured in the DMEM medium with different level of fetal bovine serum. As the results, this hybridoma line grow in the DMEM medium containing 10% fetal bovine serum is five times faster than in the DMEM medium with 1% fetal bovine serum. The maximum of the cell density are 11.106 cells/ml after 50 hours innoculation. The maximum of the titer from culture supernatant are 1/1024 after 100 hours innoculation. The monoclonal antibodies derived from hybrid cell line A6G11C9 are IgM heavy chain and the kappa light chain